2016
DOI: 10.1002/2211-5463.12055
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1 receptor blocker telmisartan induces apoptosis and autophagy in adult T‐cell leukemia cells

Abstract: Adult T‐cell leukemia/lymphoma ( ATL ), an aggressive T‐cell malignancy that develops after long‐term infection with human T‐cell leukemia virus ( HTLV ‐1), requires new treatments. Drug repositioning, reuse of a drug previously approved for the treatment of another condition to treat ATL , offers the possibility of reduced time and risk. Among clinically available angiotensin II receptor blockers, telmisartan is well k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 55 publications
1
19
1
2
Order By: Relevance
“…The main mechanism associated with antitumor effect by telmisartan treatment has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines, including prostate ( 8 ), renal ( 9 ), endometrial ( 6 ) and colon ( 10 ) cancer lines. More recently, telmisartan induced cell cycle arrest in hematologic and non-hematologic malignancies including our study ( 5 , 11 ).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…The main mechanism associated with antitumor effect by telmisartan treatment has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines, including prostate ( 8 ), renal ( 9 ), endometrial ( 6 ) and colon ( 10 ) cancer lines. More recently, telmisartan induced cell cycle arrest in hematologic and non-hematologic malignancies including our study ( 5 , 11 ).…”
Section: Introductionsupporting
confidence: 51%
“…According to previously controversial clinical studies, the antitumor effect of telmisartan remains inadequately known. Moreover, in previous studies, telmisartan has been shown to inhibit proliferation of various cancer cells ( 31 33 ) in vitro and tumor growth in vivo ( 5 7 ). However, there are no any studies on antitumor effects of telmisartan CCA date.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Telmisartan has been shown to inhibit cell proliferation by inducing apoptosis in various cancer cell lines including endometrial ( 12 ), prostate 17), renal ( 18 ) and colon ( 19 ) cancer cell lines. Although telmisartan induces cell cycle arrest in hematological malignancies ( 20 ), few studies have examined the main antitumor effects of telmisartan, other than apoptosis, on cell cycle arrest in non-hematological malignancies. As shown in our previous study, telmisartan inhibits human esophageal adenocarcinoma cell proliferation and tumor growth by inducing cell cycle arrest through the regulation of cell cycle-related proteins via the AMP-activated protein kinase (AMPK)/mammalian target of rapamycin (mTOR) pathway ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It was reported that TLM has antiproliferative effect on leukemia cell lines and ex vivo peripheral blood monocytes, and also, TLM causes autophagy and apoptosis by caspase activation. 4 Besides being an ARB, TLM is also described as a peroxisome proliferator-activated receptor (PPAR)-gamma activator and in some studies its anti-tumor activity is linked to PPAR-gamma activation. [1][2][3] Intra peritoneal administration of TLM to human endometrial tumor bearing nude mice showed that treatment with TLM inhibited tumor growth significantly.…”
Section: Introductionmentioning
confidence: 99%